Coaching and Mentoring Practices in Employee Performance Development Efforts through Work Motivation - Ahmad Rifaldhi (Jurnal Ragam Pengabdian, 2026)
This research explores the impact of coaching and mentoring practices on employee performance development through work motivation. The study aims to understand how these practices influence employee motivation and enhance performance within organizations. A literature-based methodology was employed, analyzing secondary data from books, journals, and previous studies on coaching, mentoring, and work motivation. The findings indicate that coaching and mentoring, when aligned with organizational culture and integrated with other development initiatives, significantly improve employee performance. However, challenges such as inconsistent implementation and lack of mentor training were identified. The study concludes that effective coaching and mentoring programs can build a motivated, high-performing workforce, contributing to long-term organizational success.